Hepatopancreas Transcriptome Profiling Analysis Reveals Physiological Responses to Acute Hypoxia and Reoxygenation in Juvenile Qingtian Paddy Field Carp Cyprinus carpio var qingtianensis - Qi, Ming; Wu, Qianqian; Liu, Tao; Hou, Yiling; Miao, Yixin; Hu, Menghong; Liu, Qigen (Frontiers in Physiology, 2020)
The Qingtian paddy field carp (Cyprinus carpio var qingtianensis) is a local carp cultivated in the rice field of Qingtian county, Zhejiang province, China. Its high tolerance to hypoxia makes it an ideal organism for studying the molecular regulation mechanism during hypoxia process as well as reoxygenation following hypoxia in fish. In this study, we counted the differentially expressed genes (DEGs) altered during hypoxic exposure and reoxygenation process. The results indicated that 2236 genes (1506 up-regulated genes and 730 down-regulated genes) were differentially expressed between the control and hypoxic groups. The results from Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicated that 1152 of 2236 genes were enriched, and those genes participated in energy metabolism, reactive oxygen species (ROS) elimination, acceleration of cell apoptosis, inhibition of growth, and other processes. We found activation of the pentose phosphate pathway in hypoxia treatment, suggesting that carbohydrates not only provide energy for metabolism but also provide NADPH for protecting the body from oxidative damage and ribosomes for promoting RNA synthesis. During reoxygenation, 4509 genes (1865 up-regulated genes and 2644 down-regulated genes) were differentially expressed. The results of KEGG enrichment analysis indicated that 2392 of 4509 genes were enriched, and participated in pyruvate and lactic acid metabolism, synthesis of amino acids and lipids, inhibition of cell apoptosis, regulation of cell growth and differentiation, and other processes. These differentially expressed genes effectively alleviate the body acidosis and promote the normal growth and development of the body. Through the analysis of KEGG pathway enrichment, we observed that the physiological regulation of Qingtian paddy field carp during the processes of hypoxia and reoxygenation is not a simple and reversible process. This work first reported the adaptive mechanism of hypoxia and the recovery mechanism of reoxygenation after hypoxia in common carp, and also provided new insights for the physiological regulation of fish under hypoxia treatment.